Analysis of biomedical materials and parts: Advanced nano(micro)-characterization by neutron beam techniques - Massimo Rogante (Zaštita Materijala)
The progress of the study of biomedical materials and devices, as well as their advancement, especially depend on the application of efficient characterization techniques to evaluate key physical parameters connected to performances, damage and quality. A main aim is to establish correct relationships between macroscopic functional properties and nano(micro)-characteristics. Numerous invasive biomedical devices, e.g., as planned to remain in the human body for the entire life of the patient, once implanted, operate in the ionic environment of the blood and in contact with the released substances and cells. The consequent effects must be added to the other aging factors: the dynamic stress of the pulsation is one of these effects and concerns the operational of self-expandable stents installed in arteries such as the carotid to correct stenosis. Neutron beam techniques are an excellent tool to study materials and parts of biomedical interest, contributing to solve important questions linked with the methodological restrictions of the analysis methods generally adopted: their results, complementarily, can help improving quality and functionality. This paper concerns the advanced nano(micro)-characterization of biomedical materials and parts by these non-destructive and non-invasive nuclear methods. Some examples related to the biological field are also mentioned. For applications in the biomedical and in the industrial sectors, the Rogante Engineering Office has developed particular methodological approaches and dedicated processing and treatment procedures.